2012
DOI: 10.1200/jco.2012.42.8011
|View full text |Cite
|
Sign up to set email alerts
|

Importance of Health Information Technology, Electronic Health Records, and Continuously Aggregating Data to Comparative Effectiveness Research and Learning Health Care

Abstract: Rapidly accumulating clinical information can support cancer care and discovery. Future success depends on information management, access, use, and reuse. Electronic health records (EHRs) are highlighted as a critical component of evidence development and implementation, but to fully harness the potential of EHRs, they need to be more than electronic renderings of the traditional paper medical chart. Clinical informatics and structured accessible secure data captured through EHR systems provide mechanisms thro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
96
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 134 publications
(96 citation statements)
references
References 25 publications
0
96
0
Order By: Relevance
“…In addition, aggregation of EHR data across practices could enable more efficient hypothesis testing and comparative effectiveness research in order to improve patient care, especially in combination with real-time analytics. 138 The hope is that, eventually, de-identified EHR data will become a source of clinical data not currently available from either surveys or claims. However, much work remains to ensure that information is consistently collected in a useful format for analysis.…”
Section: Priorities For Future Data and Researchmentioning
confidence: 99%
“…In addition, aggregation of EHR data across practices could enable more efficient hypothesis testing and comparative effectiveness research in order to improve patient care, especially in combination with real-time analytics. 138 The hope is that, eventually, de-identified EHR data will become a source of clinical data not currently available from either surveys or claims. However, much work remains to ensure that information is consistently collected in a useful format for analysis.…”
Section: Priorities For Future Data and Researchmentioning
confidence: 99%
“…HIT is seen as a tool that has the potential of improving the healthcare -and health -of our nation. Improvements in quality and efficiency of care (cornerstones of lean) are seen as inevitable with the implementation of HIT like "pharmacy systems, research and registry databases, practice management systems such as billing and scheduling, and patient devices" [Miriovsky et al, (2012), p.1]. It is true that information management is an integral part of care delivery and that technology may be able to help improve this component of the healthcare process.…”
Section: Electronic Health Records: An Effective Part Of Lean Practice?mentioning
confidence: 99%
“…As with many organisational change initiatives, there is usually a loss of clinical efficiency after the EHRs are put to use, which may or may not level out (Miriovsky et al, 2012). While it is often projected that increases in efficiency will come about over time as providers become familiar with the EHR system (though the lack of long-term evaluations make this future uncertain), some studies have found that physicians spend more time on computer-related activities and thus spend less time on face to face interactions with the patient.…”
Section: Electronic Health Records: An Effective Part Of Lean Practice?mentioning
confidence: 99%
See 2 more Smart Citations